On generalized fractional integral inequalities for the monotone weighted Chebyshev functionals - Rahman, Gauhar; Nisar, Kottakkaran Sooppy; Ghanbari, Behzad; Abdeljawad, Thabet (Advances in difference equations, 2020)
In this paper, we establish the generalized Riemann–Liouville (RL) fractional integrals in the sense of another increasing, positive, monotone, and measurable function Ψ . We determine certain new double-weighted type fractional integral inequalities by utilizing the said integrals. We also give some of the new particular inequalities of the main result. Note that we can form various types of new inequalities of fractional integrals by employing conditions on the function Ψ given in the paper. We present some corollaries as particular cases of the main results.